Effect of Tamarind Turmeric Drink on Dysmenorrhea in Women of Reproductive Age: Efek Pemberian Minum Kunyit Asam terhadap Dismenore pada Wanita Usia Subur - Rizky, Rizky Putri Amalia; Dinengsih, Sri; Kundaryanti , Rini (Jurnal Kebidanan Midwiferia, 2023)
Women of childbearing age experiencing menstruation experience physical discomfort on the eve of or during menstruation including menstrual pain called dysmenorrhea that occurs during menstruation due to uterine muscle spasms. Drug treatments and supplements are commonly used to treat menstrual cramps. Turmeric and tamarind drink is a menstrual cramps treatment that is safe, easy to use and has no side effects. The active ingredients in turmeric function as antioxidants, anti-inflammatory, and pain relievers, while tamarind (tamarind) fruit contains antioxidants, anti-inflammatory drugs, antipyretics, and sedatives. Therefore, drinking tamarind turmeric water can reduce the severity of menstrual cramps. Objective: to determine the effect of giving tamarind turmeric drink on the incidence of dysminorrhea in women of childbearing age at TPMB "N" in 2023. Method: This study used a quasi-experimental design with a pre-test and post-test design, and the sampling technique was purposive sampling with a total sample size of 28 respondents... using the NRS scale. Using the NRS scale. The analysis used is the Wilcoxon and Mann Whitney Test. Research Results: There is an effect of giving tamarind turmeric drink on dysminorrhea in WUS with a p-value (0.001 <0.05) Conclusion: Drinking tamarind and turmeric can reduce the severity of menstrual pain in women of childbearing age at TPMB N Year 2023. Suggestion: It is expected that WUS can utilize sour turmeric drink as an alternative treatment to reduce dysmenorrhea which can be consumed before menstruation or during menstruation